Are there any factors influencing the course of multistage treatment in Hirschsprung’s disease? - Sosnowska, Patrycja; Błaszczyński, Michał; Moryciński, Sebastian; Porzucek, Witold; Mańkowski, Przemysław (Gastroenterology Review/Przegląd Gastroenterologiczny, 2016)
Introduction : Surgical treatment of Hirschsprung’s disease may be performed in a single step, or in stages with a temporary stoma. The therapy depends on the clinical condition of the patient and the severity of symptoms. Planned multistage treatment is carried out in two or three steps. Aim : To analyse our 15 years of experience with multistage surgery for the treatment of Hirschsprung’s disease, to identify multistage-related factors influencing the course of surgery and hospitalisation, and to evaluate the probability of complications during multistage treatment. Material and methods: The study material was collected on the basis of documentation of patients treated during the years 2000 to 2014. The parameters concerning surgery and hospitalisation were statistically analysed. Results: Twenty nine patients were treated with multistage surgery using the following methods: Duhamel-Martin and Transanal Endorectal Pull-Through (TEPT). There were significant correlations (p < 0.05) between length of resected intestine and operative time. Classification and Regression Tree (CRT) was used to classify the operated children depending on the presentence of complications after surgery. Conclusions : The incidence of complications during multistage treatment for both methods was comparable. It is difficult to objectively compare the Duhamel-Martin and TEPT techniques because of the different indicators for their use in multistage surgery. Intestinal adhesions were the most common complication after definitive surgery. Younger age of the operated patients was associated with greater risk of adhesion formation.